Truth and Existence in Hegel and Thomas Aquinas - Espiña, Yolanda (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
Existence constitutes a challenge for the relationship between thought and reality. This problem is approached through an approximation between Hegel and Thomas Aquinas, as both place the truth in the realm of the intelligible. Reality, by summoning existence, also calls for a reflection on intelligibility. In Aquinas existence is a necessary condition for intelligibility; Hegel appeals to intelligibility as a necessary condition for existence. The metaphysical dimension of this (diachronic) discussion culminates in the question of the existence of God.
Keywords: truth; existence; Hegel; Thomas Aquinas; ontological argument